Skimming and Scanning Strategies in Enhancing High School Students' Reading Skills by Using TOEFL Questions - Theodesia Lady Pratiwi; Jennifer Wiwit; Maya Marsevani (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
This study examines the effectiveness of skimming and scanning strategies in enhancing students' TOEFL reading skills. Conducted through Classroom Action Research (CAR), the study involved 36 eleventh-grade students from a private high school in Batam. Participants were selected using a purposive sampling technique, assisted by the former teacher. The research was carried out in four stages: planning, action, observation, and reflection. A pre-test and a post-test were administered to evaluate student progress, along with field notes to document classroom observations. The effectiveness of the intervention was assessed by comparing the pre-test and post-test results. The findings revealed a statistically significant improvement in students' TOEFL reading comprehension. The average pre-test score increased from 69.47 to 82.23 in the post-test, which is classified as